Multi-Religious Education from the Perspective of Islamic Teachings Compared to the Pluralist Model - Toosi, Javad Fakhkhar; Jamil, Asyraf Isyraqi (Afkar: Jurnal Akidah dan Pemikiran Islam, 2021)
The article illustrates the capacity of Islam to solve the social problem of religious education in multicultural societies. A qualitative method has been adopted. The main result of the study is that in societies where people of different religions live. Islam, based on its beliefs, accepts multi-religious education that is to educate all religion’s teachings. This side of Islamic heritage solves the social problem that comes from teaching a particular religion in such societies. The study displays that the pluralistic religious education, cannot solve these problems. The study concludes that Islam has an active and constructive approach to other cultures and religions in the field of education that is based on freedom of religion and educational justice. It also suggests that some practical researches should be done to explore the benefits of this Islamic solution in Malaysian society as a multicultural society.